Revisiting Issues Relating to the Content of Ownership Rights, as Exemplified By the Legislation of Russia and other Countries - S. Bondarenko, Sergey; V. Mikhnevich, Anna; V. Tychinin, Sergey; E. Tonkov, Evgeny; I. Chesovskoy, Evgeny (International Journal of Criminology and Sociology, 2022)
Given article takes into consideration the approaches to the disclosure of the ownership rights content existing in different legal systems. The idea of disclosing the ownership rights content through a specific set of owner’s powers exists in the legal systems of various countries. In this case, the number of legal powers may differ, as well as an understanding of each of them. The triad of owner’s powers (possession, use, disposal), enshrined in the laws of Russia and a number of other countries, is analyzed in details. The views regarding the construction of a theoretical model of the content of ownership rights were expressed.